Comparative Study of Radionuclide Uptake Levels between Primary and Metastatic Bone Tumors - Huguette, Yigbedeck; Kwame, Kyere; Kojo, Wilson; Francis, Hasford; Kwabla, Sosu; Otoe, Ankrah (World Journal of Nuclear Medicine, 2014)
Study on 95 patients to compare radionuclide uptake levels in patients undergoing bone scintigraphy at a Nuclear Medicine Unit has been performed quantitatively using Image J software. Patients were administered with activity ranging from 0.555 to 1.110 MBq depending on their body weight, and their whole-body bone scans obtained with an installed e.cam single-photon emission computed tomography system. Matrix size of 256 × 1024 was used in acquiring the scintigrams. Quantitative analyses performed with installed Image J software revealed higher radionuclide uptake levels in metastatic tumors compared with primary tumors for all selected skeletal parts. Average normalized count of activity in metastatic tumors was 37.117 ± 27.740 cts/mm 2 /MBq and its corresponding uptake in primary tumors was 23.035 ± 19.542 cts/mm 2 /MBq. The relative higher uptake in metastatic tumors over primary tumors could be attributed to higher osteoblastic activity and blood flow in metastatic tumors.
Keywords: Counts of activity; diagnosis; metastatic tumor; primary tumor; quantitative assessments; radionuclide; scintigraphy; single-photon emission computed tomography; therapeutic